DEVELOPMENT OF AN IMPULSE BUYING MODEL IN SOCIAL COMMERCE-BASED SHOPPING ACTIVITIES - M. Adhitya A. Walenna, A.
The presence of technology has changed shopping behavior from traditional commerce to digital commerce or electronic commerce. Social media, which was originally a place to share activities, is now transformed into a new trading space known as social commerce. Social commerce is a method of shopping using social media platforms (Tiktok, Facebook, Instagram, Twitter, etc.). Social commerce uses a combination of social media and e-commerce functions to conduct commercial activities by utilizing online social capital on social media. Using social media for a long period of time and the experiences shared by others trigger a sudden and often irresistible urge to buy called impulsive buying. Impulsive buying is an unplanned purchase when a customer feels the urge to buy a product or service suddenly. As social commerce grows, the number of sales is increasing so merchants need a good strategy in creating content to stand out from the crowded online marketplace. The purpose of this study is to propose a model that can explain the urge to buy impulsively on social commerce. This research analyzes customer characteristics that can lead to impulse purchases. This research identifies the factor that the richness of available information affects both cognitive and affective reactions. Interaction factors are also investigated to determine any influence on impulse buying. This study uses 232 user sample data who have made purchases of fashion products